TPI lead induced cardiac perforation, a nightmare and change of practice - Gautam, Samir; Dhungel, Sachin; K C, Bishal; Khan, Majhar; Shakya, Abhishesh; Panjiyar, Rajesh; Sharma, Deepanjali (Journal of National Heart and Lung Society Nepal, 2026)
SUMMARYInferior wall myocardial infarction is usually associated with bradycardia. Even sometimes they present with complete heart block or variable degree of heart block. We used to put temporary pacemaker whenever there was significant bradycardia with second or third degree heart block. It used to ease us to deal with bradycardia and hypotension which is usual during percutaneous intervention to right coronary artery. We had nightmare of acute cardiac tamponade and shock following removal of temporary pacemaker lead after successful PCI. Immediate bedside pericardiocentesis was done with fluid resuscitation with survival of patient. This made us change of practice to treat bradycardia and hypotension during PCI with medication rather than with TPI.Key Words: Acute MI, Inferior wall, Temporary Pacemaker, Cardiac Tamponade